Under the influence of the Sun: how space weather affects our planet - Valio, Adriana (Cadernos de Astronomia, 2024)
Our star, the Sun, exhibits magnetic activity in the form of dark spots on its surface, and also produces flares and mass ejections from its atmosphere. This article delves into the dynamics of the Sun and its effects on the Solar System, especially on Earth. The solar atmosphere, which includes the photosphere, chromosphere, transition region, and corona, along with the solar wind play a crucial role in understanding solar activity. The Sun’s magnetic field, the energy source of solar activity, is discussed in detail, including sunspots and the 11-year cycle, as well as notable grand minima such as the Maunder Minimum and its impact on Earth’s climate. Solar flares and coronal mass ejections are major drivers of space weather, affecting various aspects of the Earth’s environment. Energetic particles from flares and mass ejections interact with the terrestrial magnetosphere, leading to geomagnetic storms that can significantly impact technological systems. These storms can cause satellite malfunctions, communication systems failures, blackouts, and auroras, as well as affect the ionosphere. Understanding solar active phenomena is essential for improving space weather predictions and mitigating the impacts of solar-related events on modern technology and infrastructure.